FACING ONLINE LEARNING PROBLEMS THROUGH CHARACTER BUILDING, A TEACHER STRATEGY - Sita Aulia Rahmah; Siti Komariah; Siti Nurbayani K (Nurul Jadid University, 2021)
The pandemic has been putting pressure for us to make a big digital leap, in an instant, education changed as if it’s a digitalization remote, forces pupils to manage and master digital device in order to participate in education, and it’s not just the pupils who adhere to these changes, but also the teachers, schools, families, even society. This online learning system demands teachers’ role, even more, bestowing the measurement of a successful online learning process, which determined by the teacher, creativity enhancement so that learning becomes interesting with the fully online e-learning format learning method. This case study research will examine teachers’ strategies to overcome problems that arise in online learning through character building. This research purpose is to describe educator roles in overcoming online learning problems through character building. This research captures its data through observations, in-depth interview, documentation study and literature study. Furthermore, this research uses data reduction, data display, and conclusion drawing as methods of analysis. To test the reliability of the data, this research uses data, method and source triangulation. The result of this research shows that teachers and pupils collaboration through its creativity is a must, one of it is to involve OSIS as an activity partner.